Progesterone/Oestradiol ratio can better predict intracytoplasmic sperm injection outcomes than absolute progesterone level - Reda S Hussein; Ihab Elnashar; Hisham A Abou-Taleb; Yulian Zhao; Ahmed M Abdelmagied; Ahmed M Abbas; Osama S Abdalmageed; Ahmed A Abdelaleem; Tarek A Farghaly; Ahmed A Youssef; Esraa Badran; Mostafa N Ibrahim; et al. (Wolters Kluwer Medknow Publications, 2021)
Background: Several parameters were proposed to predict the impact of premature luteinization on intracytoplasmic sperm injection (ICSI) outcomes such as isolated progesterone (P) level, progesterone to oocyte ratio, and progesterone/estradiol ratio (P/E2). Aim: The aim of this study is to compare the predictive value of P/E2 ratio and isolated P level on the ovulation triggering day for pregnancy outcomes in fresh GnRH antagonist ICSI cycles. Settings and Design: A retrospective cohort study conducted in a university-affiliated in vitro fertilization center between January 2017 and April 2019. Methods: The study included women who underwent their first- or second-ranked GnRH antagonist ICSI cycles with day-3 embryo transfer. P/E2 ratio was calculated as (P [ng/mL] × 1000)/E2 (pg/mL). Cutoff values of ≥1.5 ng/ml for high P (HP) and ≥0.55 for HP/E2 ratio were chosen based on the literature. Statistical Analysis: A receiver operating curve was performed to detect the predictability of serum P/E2 and P for the ongoing pregnancy rate. First, patients were divided according to either P level (low P < 1.5 ng/mL and HP ≥1.5 ng/mL) or P/E2 ratio (low P/E2 <0.55 and HP/E2 ≥ 0.55). Patients were further divided into four subgroups: (Group A: HP and HP/E2 ratio, Group B: low P and low P/E2 ratio, Group C: HP only, and Group D: HP/E2 only). A multivariate regression analysis models were used to account for the effect of the cycle confounders on the likelihood of pregnancy. Results: A total of 402 ICSI cycles were analyzed. The area under the curve was 0.67 and 0.59 for P/E2 and P, respectively. P/E2 showed a significant association with ongoing pregnancy (adjusted odds ratios [aOR]: 0.409, 95% confidence interval [CI] 0.222-0.753, P = 0.004) while HP revealed no significant predictive value (aOR: 0.542, 95% CI 0.284-1.036, P = 0.064) after the multivariate analysis. Conclusions: P elevation may not present as an independent predictor for cycle outcomes. P/E2 ratio has a better prognostic value than P alone in predicting pregnancy of GnRH antagonist cycles.